Herre og drott - konge og sjøkonge karmøyseminaret 2022 - Skre, Dagfinn (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
Avaldsnes on Karmøy in Rogaland, which according to Snorre was King Harald Fairhair's royal estate, has been the center of a major research effort since 2007. Extensive excavations have, among other things, uncovered the remains of a lordly settlement from the AD 200s-400s and the ruins of a royal masonry complex from around AD 1300. Important insights have been gained about the place, the region, and the history of the Norwegian kingdom, and the results are also of significance for international scholarly debates. The papers in this book are based on lectures from the Karmøy Seminar 2022, and have a joint spotlight on the nature of lordship and kingship. The themes range from tribal societies in Roman times via the first kings of the Viking Age to the Norwegian kingdom's collapse at Håkon 6. Magnusson's death in 1380. Prominent professionals from Norway, Sweden and England discuss, among other things, the migrations of Ryger, Goths, and other tribes in the continent in the first centuries AD, the queens and queen mothers of the Viking Age, Harald Fairhair's overseas contacts, and the Norwegian kingship's roots in Nordvegen, the sailing route along the western coast of the Scandinavian Peninsula. The papers are written to be readable by scholars as well as the interested public.